Electronically integrated mesoporous Ag-TiO2 nanocomposite thin films for efficient solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Nalajala, Naresh; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Technology, 2021)
The synthesis of mesoporous TiO2 by a solution-based assembly process and Ag/TiO2 nanocomposites is provided. The efficacy of Ag/TiO2 nanocomposite as photocatalyst in thin-film form is demonstrated for solar hydrogen generation in sunlight. Integration of Ag with TiO2 dramatically enhanced the H-2 production: with 1 wt% Ag on TiO2 (TiAg-1), the H-2 yield was observed to be 4.59 mmol h(-1) g(-1), which is 2.3 (30) times larger than 0.5 wt% Ag on TiO2. TiAg-1 shows 4.3 times higher activity in film form compared with its powder counterpart. High photocatalytic efficiency is attributed to the surface plasmon resonance effect of Ag, electronic integration of Ag with TiO2, and subsequent valence band broadening, large distribution of Ag nanoparticles and abundant Ag-TiO2 Schottky junctions, and the later minimizes electron-hole recombination. Interparticle mesoporous network increases necking and the high surface area offers easy accessibility of the reactants to a large number of active sites.
Keywords: heterogeneous catalysis; heterojunctions; plasmon effect; Silver; solar energy conversion; Solar hydrogen

Facile one-pot synthesis of Cu x O/TiO2 photocatalysts by regulating Cu oxidation state for efficient solar H2 production - Rajendran, Sivaraj; Mani, Sunesh S.; Nivedhitha, Thazhath R.; Asoka, Anantha Krishnan; Arun, Pushkaran S.; Mathew, Thomas; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2023)
Development of highly efficient CuxO/TiO2 photocatalysts by regulating the oxidation state of Cu exclusively in either single or mixed oxidation state(s) is desirable but difficult to achieve without employing any external reagents. The present work describes a one-pot synthesis strategy to obtain CuxO/TiO2 photocatalysts with Cu in +1 and/or +2 by using a suitable combination of ethylene diamine tetra acetic acid (EDTA) and ethylene diamine, carefully varying the Cu content, and heat treatment process. CuxO/TiO2 nanocomposite catalysts were characterized thoroughly by physicochemical methods. Textural analysis indicates a high dispersion of CuxO on porous TiO2 with p-n heterojunctions between them in CuxO/TiO2 catalysts. UV-visible spectral analysis suggests the presence of CuxO on TiO2 with significantly extended absorption from the UV to the visible region. X-ray photoelectron spectroscopy (XPS) analysis indicates a strong synergetic interaction between TiO2 and CuxO due to the comparable CB potential and p-n heterojunction at the interface among them. Photoelectrochemical studies demonstrate excellent charge-carrier separation efficiency, low charge-transfer resistance, and high double-layer capacitance with Cu2O/TiO2 photocatalysts. Photocatalytic efficacy of a CuxO/TiO2 nanocomposite in thin-film form has been demonstrated for solar hydrogen generation in sunlight. The incorporation of Cu+ in TiO2 largely improves the H-2 production, and all of the CuxO/TiO2 nanocomposites in thin-film form exhibited higher efficiency compared to their particulate/suspension counterpart. Among the composite catalysts, TiCu-1 in thin-film form, with Cu exclusively in +1 oxidation state, exhibited a high hydrogen production rate of 7.06 mmol/hg, which is 6 times higher than its suspension counterpart; also catalysts containing mixed Cu-oxidation states exhibited about 60-70% activity as that of TiCu-1. The superior performance of Cu2O/TiO2 nanocomposites in thin-film form was due to their enhanced light harvesting ability, high mass transfer rate, and easy accessibility of the reactant species to the active sites.
Keywords: heterojunction; Photocatalysis; Solar hydrogen; thin film; titania

Bimetallic and plasmonic Ag and Cu integrated TiO2 thin films for enhanced solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Arun, Pushkaran S.; Vijaykumar, Aparna; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Advances, 2024)
<div class="abstract author" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle-integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation in sunlight. Integration of Ag + Cu on TiO2 significantly enhances the solar H2 production due to the combined SPR effect of both metal species and the possible synergistic interaction among Cu + Ag in Ag–Cu/TiO2. TiAgCu-1 (0.75 wt% Ag and 0.25 wt% Cu on TiO2) showed the highest H2 yield of 6.67 mmol h−1 g−1 and it is 43 times higher than that of bare TiO2. The thin-film form of TiAgCu-1 shows 5 times higher solar H2 production than its powder counterpart. 1 wt% of Ag or Cu on TiO2 shows a H2 yield of 4.6 or 2 mmol h−1 g−1, respectively, which underscores the importance of combined or synergistic effects. The increase in solar H2 generation in Ag–Cu/TiO2 is attributed to factors such as the SPR effect of Cu and Ag, and strong interaction between Ag and Cu. The high photocatalytic efficiency of the TiAgCu-1 thin film is attributed to the large dispersion of metallic species with relatively high Ag/Cu surface atomic ratio, enhanced light absorption, a heterogeneous distribution of Ag and Cu species, and high double layer capacitance. The inter particle mesoporous network increases the interfacial charge transfer and reduces the mass transfer limitations. The plausible photocatalytic reaction mechanism could involve the combination of direct electron transfer from metal (Cu/Ag) to TiO2 as well as the significant field effect due to the Ag–Cu alloy, which is expected to increase the electron excitation locally. <div class="abstract graphical" id="aep-abstract-id9" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation.

Review on the recent advances in the design and structure–activity relationship of TiO2-based photocatalysts for solar hydrogen production - Mani, Sunesh S.; Rajendran, Sivaraj; Mathew, Thomas; Gopinath, Chinnakonda (Energy Advances, 2024)
The major issues that determine the efficiency of photocatalyst composite materials for solar hydrogen production, with or without a sacrificial agent, are efficient visible light harvesting properties, efficient separation of charge carriers and their utilization of redox sites, and stability. Thus, significant efforts have been devoted in the past few decades to modify the above characteristics by integrating constituent components of composites using different approaches. In the present review, we aim to summarize the recent advances, predominantly, in the area of TiO2-based photocatalyst composites for solar hydrogen production. Firstly, we present the recent progress in material integration aspects by discussing the integration of TiO2 with different categories of materials, including noble/3d metals, metal oxides/sulphides/selenides, other low bandgap semiconductors, C-based materials, and dye sensitizers. Furthermore, we discuss how material integration helps in tailoring the electronic and optical properties for activity tuning in solar H2 production. Subsequently, critical changes in the physico-chemical and electronic properties of composites with respect to their preparation methods, morphology, crystallographic facets, particle size, dopant, calcination temperature, and structure–activity relationship to solar hydrogen production are addressed in detail. Moreover, we discuss the importance of fabricating a photocatalyst in a thin film form and performing solar hydrogen production in different reactor set-ups for enhancing its photocatalytic performance, while addressing device scalability. Despite the significant advancements made in this field, solar-to-hydrogen conversion efficiency still needs to be improved to realise the practical application of solar hydrogen production. In this case, the direct conversion of water to hydrogen via overall water splitting and renewable H2 production from wastewater or biomass components by employing suitable photocatalysts are some possible ways to improve the energy efficiency, and continuous research in the above directions is highly desirable.

Mesoporous Fe2O3-TiO2 integrated with plasmonic Ag nanoparticles for enhanced solar H2 production - Mani, Sunesh S.; Rajendran, Sivaraj; Saju, Simi; Babu, Bindhya M.; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2025)
Present work describes a sol-gel assisted one-pot synthesis of mesoporous Fe2O3-TiO2 nanocomposites (TiFe) with different Ti : Fe ratios, and fabrication of Ag-integrated with TiFe nanocomposites (TiFeAg) by a chemical reduction method and demonstrated for high solar H2 generation activity in direct sunlight. Enhanced solar H2 production is attributed to the light absorption from entire UV+Visible region of solar spectrum combined with Schottky (Ag-semiconductor) and heterojunctions (TiO2-Fe2O3), as evidenced from HRTEM and various characterization studies. TiFeAg-2 thin film (1 wt % Ag-loaded TiFe-4) displayed the highest activity with a solar H2 yield of 7.64 mmol h-1g-1, which is 48 times higher than that of bare TiO2 and 5 times higher in thin film form compared to its powder counterpart. Schottky and heterojunctions formed at the interface efficiently separate the charge carriers and increase the hydrogen production activity. The highest H2 production activity of TiFeAg-2 is partly attributed to the heterogeneous distribution of Fe3+ and metallic Ag-species with relatively high Ag/Ti surface atomic ratio. A plausible photocatalytic reaction mechanism on TiFeAg nanocomposite may involve the direct electron transfer from both Fe2O3 and TiO2 to Ag nanoparticles which are subsequently utilized for the reduction of H+ to H2.
Keywords: energy conversion; green hydrogen; Photocatalysis; Solar harvesting; water splitting

Multifunctional NiO/Ti3+-TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e- and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p-n heterojunction formation between NiO and Ti3+-TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+-TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni-Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+-TiO2 nanocomposites. EXAFS studies show that the Ni-O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+-O-Ti3+/Ti4+ lattice network. Ni2+/Ti3+-TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C-C cleavage of glycerol. The NiO/Ti3+-TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+-TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h-1 g-1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+-TiO2, formation of a p-n heterojunction at the interface between NiO and Ti3+-TiO2 and effective utilization of charge carriers for redox reactions.

Multifunctional NiO/Ti3+–TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e− and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p–n heterojunction formation between NiO and Ti3+–TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+–TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni–Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+–TiO2 nanocomposites. EXAFS studies show that the Ni–O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+–O–Ti3+/Ti4+ lattice network. Ni2+/Ti3+–TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C–C cleavage of glycerol. The NiO/Ti3+–TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+–TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h−1 g−1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+–TiO2, formation of a p–n heterojunction at the interface between NiO and Ti3+–TiO2 and effective utilization of charge carriers for redox reactions.